ANALYSIS OF PREMIUM INCOME RECOGNITION AND CLAIM EXEMPTION BASED ON PSAK NO.36 AT PT ASURANSI MULTI ARTHA GUNA TBK (AMAG) - Fadhila Khairani Husna; Yuyun Wahyuni; Zulfa Riza; Muhammad Haykal; Aziz Nuraziz (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the recognition of premium income and claim expenses on the anallis of premium income recognition and free claims at PT Asuransi Multi Artha Guna Tbk whether it is in accordance with PSAK No. 36. The type of research used in this study is qualitative method. Quantitative methods are research that is descriptive and tends to use analysis. The data processed are the Company's Financial Statements and interviews conducted by the author with PT Asuransi Multi Artha Guna Tbk. The data collection technique used is library research, Based on the results of the interviews that have been conducted, it can be concluded as follows: (1) The recognition of premium income of AJB Bumiputera Makassar is in accordance with PSAK No. 36, because for short-term contract premiums, the company recognizes income in accordance with what has been regulated in PSAK No. 36, namely when the contract has been agreed by both parties as well as premiums other than short-term contracts, The Company recognizes income at maturity from the Policyholder by giving the Client the obligation to pay the fee at the time the Client renews the contract. (2) The recognition of claims expense of AJB Bumiputera Makassar is in accordance with PSAK No. 36 where the expense is recognized when the claim has been approved, claims in the settlement process and claims that occur but have not been reported